China contributed to low-carbon development: carbon emission increased but carbon intensity decreased - Huang, Chunbo; Gan, Xintao; Wan, Yunshan; Jin, Lin; Teng, Jiaxi; Li, Zeyu (Frontiers in Ecology and Evolution, 2024)
Population expansion and economic development increased global greenhouse gas emissions, leading to frequent environmental degradation events such as glacier melting, sea level rise, and extreme weather, which seriously threaten the survival and development of human beings.China, the world's largest developing country and promoter of the "Belt and Road Initiative" (BRI), accounts for 28.8% of the world's total energy carbon emissions. How to reduce energy consumption to achieve the "double carbon" target (i.e., carbon peaking and carbon neutrality) and promote the implementation of Green BRI is still a serious challenge that China needs to face. Therefore, this study evaluated China's carbon emissions using three indicators (i.e., total carbon emission, carbon intensity, and carbon emissions effect), and used spatial analysis to reveal the spatial and temporal trends of China's carbon emissions. In addition, the LMDI model was adopted to explore the driving mechanism of carbon emissions, so as to seek a path that can achieve harmonious economic and environmental development, as well as the "double carbon" target. The results indicated that China's total carbon emission increased at a rate of 226.12% from 2000 to 2019, while the carbon intensity decreased at a rate of 48.84%. Carbon emission in China showed a trend of increasing and then decreasing from southwest to northeast. From 2000 to 2019, the total carbon emission, Gross Domestic Product (GDP), population size and total energy consumption in China are growing in synergy. Economic and population effects are positively related to carbon emissions, while technology effects are negatively related to it, which indicated that technological innovations contribute to the reduction of carbon emissions. Based on this, we proposed some suggestions to control carbon emissions with a view to helping policy makers to formulate relevant policies. The findings of this study can provide a scientific basis and reference for the country to achieve the "double carbon" target and the low-carbon sustainable development of BRI.